A temperature-tuned electrochemiluminescence layer for reversibly imaging cell topography. Issue 46 (18th November 2022) - Ma, Cheng; Xing, Zejing; Gou, Xiaodan; Jiang, Li-Ping; Zhu, Jun-Jie
Abstract : A temperature-tuned electrochemiluminescence layer is designed for reversibly imaging single cell topography. The regulated thickness range of the ECL layer depends on the adopted ECL routes, namely the catalytic route and oxidative reduction route. Abstract : Investigating electrochemiluminescence (ECL) scenarios under different temperatures is important to expand its imaging scope near an electrode surface. Here, we develop a temperature-tuned ECL layer by recording the evolution of shadow regions of adherent cells. Finite element simulation and experimental results demonstrate that the thickness of the ECL layer (TEL) is reversibly regulated by electrode temperature ( T e ), so that single cell topography at different heights is imaged. The TEL in two ECL routes shows different regulation ranges with elevated T e, thus providing a flexible approach to adjust the imaging scope within specific heights. In addition, a heated electrode significantly improves the image quality of cell adhesion in heterogeneous electrochemical rate-determined situations. Thus, the contrast in cell regions shows a reversible response to T e . This work provides a new approach to regulate the TEL and is promising for monitoring transient heat generation from biological entities.